The Importance of Emigrant Societies: The Sava Slovenian Society of Belgrade - Poljak Istenič, Saša (Traditiones, 2010)
<span style="line-height: 115%; font-family: ’Helvetica’,’sans-serif’; font-size: 11pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-font-family: AGaramondPro-Italic; mso-ansi-language: SL; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-style: italic;">Za izseljence so njihova društva med pomembnejšimi dejavniki za negovanje materinščine in ohranjanje, oblikovanje ali utrjevanje identitete. Društvo Slovencev Sava Beograd je mlado, a aktivno; poleg kulturnih dejavnosti (predvsem v povezavi s prazniki v Sloveniji) si skupaj z drugimi slovenskimi društvi prizadeva za izvolitev nacionalnega sveta Slovencev v Srbiji. V prispevku je nakazan pomen društev za ohranjanje stika s slovenskim jezikom in kulturo, kulturno-umetniško ustvarjanje, izobraževanje, medsebojno spoznavanje in formalno združevanje slovenske manjšine v Srbiji. <span style="line-height: 115%; font-family: ’Helvetica’,’sans-serif’; font-size: 11pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-font-family: AGaramondPro-Italic; mso-ansi-language: SL; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-style: italic;">*** <span style="line-height: 115%; font-family: ’Helvetica’,’sans-serif’; font-size: 11pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-font-family: AGaramondPro-Italic; mso-ansi-language: SL; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-style: italic;">Societies are important factors for nurturing emigrants’ native languages and preserving, shaping, and strengthening their identity. The Sava Slovenian Society of Belgrade is young but active; in addition to cultural activities (connected especially with Slovenian holidays), together with other Slovenian societies it is seeking to elect a Slovenian national council in Serbia. This article outlines the importance of societies for maintaining contact with the Slovenian language and culture, as well as the cultural and artistic creativity, education, mutual acquaintanceship, and formal association of the Slovenian minority in Serbia.